Voicing up in debate competition: oral development of two Malaysian ESL learners - Amiri, Farzaneh; Othman, Moomala; Jahedi, Maryam (Canadian Center of Science and Education, 2016)
This research used a qualitative approach to focus on the classroom debate between Malaysian English second language learners (ESL). Since debate has been often perceived as not a suitable activity for low proficiency students due to their limited linguistic resources, there has not been much emphasis on the impact of debate on incompetent ESL learners; however, this study was an attempt to concentrate on two students who were not competent in English to investigate their oral development via debate. The study observed the communicative strategies employed in this challenging task during the five debate rounds. Although the progress made was quite limited, the study showed that debate competition can be a relevant and meaningful practice for speaking activity among low proficiency students. Moreover, it showed that debate can be used to scaffold students’ practice in speaking.